Persistence of hepatitis B immune memory until 9–10 years of age following hepatitis B vaccination at birth and DTaP-IPV-HB-PRP∼T vaccination at 2, 4 and 6 months. Issue 5 (4th May 2018) - Kosalaraksa, Pope; Chokephaibulkit, Kulkanya; Benjaponpitak, Suwat; Pancharoen, Chitsanu; Chuenkitmongkol, Sunate; B'Chir, Siham; Da Costa, Xavier; Vidor, Emmanuel
ABSTRACT: Objective : To evaluate the long-term persistence of anti-hepatitis B surface (HBs) antibodies and the response to a HB challenge re-vaccination in children who had received a primary series of DTaP-IPV-HB-PRP∼T (Hexaxim™) or DTaP-IPV-HB/PRP∼T (Infanrix hexa™). Methods : Two cohorts of participants who had previously received HB vaccine at birth followed by either DTaP-IPV-HB-PRP∼T or DTaP-IPV-HB/PRP∼T co-administered with PCV7 at 2, 4, 6 months of age in a randomized, Phase III, observer-blind study in Thailand, were followed up for anti-HBs antibodies (geometric mean concentrations [GMCs] and seroprotection [SP] rate [% of participants with a titer ≥10 mIU/mL]) at 12–18 months of age and 9–10 years of age. A monovalent HB challenge re-vaccination was administered at 9–10 years of age and the anamnestic response was evaluated. Results : Anti-HBs GMCs and SP rates in the DTaP-IPV-HB-PRP∼T and DTaP-IPV-HB/PRP∼T groups were high and similar post-primary vaccination series (2477 mIU/mL and 99.5% and 2442 mIU/mL and 99.5%, respectively) and declined to a similar extent in each group at 12–18 months (154.5 mIU/mL and 90.8% and 162.3 mIU/mL and 96.5%, respectively). Antibody levels further declined at 9–10 years of age (13.3 mIU/mL and 49.3% and 8.0 mIU/mL and 42.9%) and a strong anamnestic response occurred in each group post-HB challenge re-vaccination (92.8% and 98.7%, respectively). Conclusion : The kinetics of long-term anti-HBs antibody persistence were similar following a primary series of DTaP-IPV-HB-PRP∼T or DTaP-IPV-HB/PRP∼T. The response to a subsequent HB challenge re-vaccination was strong and similar in each group, demonstrating persisting immune memory.